Les nuits de Shanghaï - Wenbo Hu; Luc Gwiazdzinski; Wanggen Wan (Netcom)
This article aims to identify poles of night-time activity in the Shanghai metropolis. Using a social network known as SINA micro-blog, the “Facebook”, on which Chinese people share their personal experiences and lives, we analyse the way in which they participate in urban nocturnal activities from spatial and temporal dimensions. The analysis geolocalized is based on a geographical survey referred to here as “centripetal urban polarities”. Additional observations of the area is used to verify and understand better the dynamics of the night-time life and the spatial-temporal behaviour of individuals.